Um Estudo sobre a Estrutura e Acervo da Biblioteca Professor Severino Francisco e sua Contribuição na Formação dos Discentes do Curso de Química Licenciatura – UFNT – Araguaína. - Silva, Franciele Araújo da (Universidade Federal do Tocantins, 2024)
The Libraries play a major role in the collection of diverse information in the World. Its existence records date back to the 9th century BC, where the library of Nineveh stands out as the first library in the history of mankind. This work deals with the role of the library "Professor Severino Francisco" in the formation of undergraduates of the Chemistry course. Where the make observation about books that serves the chemistry area was carried out, as well as the relationship between students enrolled at the course with the aforementioned library and this collection, were interviewed was carried out via google forms 14 course students. The books analyzing demonstrates that, this collection is well structured, but with fragility in some areas of course such as, in inorganic chemistry that has most of the books in english and not used by the students, in the analytical there are few volumes for the area and experimental chemistry and there are few updated books. The questionnaire analyzing the applied, are observed that most of the interviewees use the library's collection in beginning of course. In general, students describe the library as a comfortable and pleasant space. However, it was observed not well used as a study environment, probably because of the lack of this culture in the region or well as the use of books in PDFs by computers or notebooks, some students have a computer /notebook and therefore do not use the computers provided by the library for study. Was possible observe that the library "Professor Severino Francisco" directly contributes to process of training students of the Chemistry Licentiate course - UFNT.